Cities-benchmarking algorithm: a meta-ranking exercise. (1st January 2012) - González, Octavio; Carrillo, Francisco Javier
The World Capital Institute uses the Most Admired Knowledge Cities (MAKCi) framework to compare cities. This framework considers other capitals than the financial one and allows to evaluate cities as knowledge cities. The MAKCi framework contains specifications about which indicators should be used; nevertheless, the same kind of information is not always available from all the cities. Besides, the data could be non-existent, restricted from public use, or hard to find. For this reason, comparing cities through the MAKCi framework becomes a major challenge. The purpose of this paper is to propose an algorithm to compare cities using reliable and available information for all the cities compared at the evaluation time.